2013
DOI: 10.1039/c2fo30178d
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-tumor activity of a polysaccharide from freshwater clam, Corbicula fluminea

Abstract: The fresh water clam Corbicula fluminea is currently one of the most economically important aquatic species in China because of its nutritional value and pharmacological activity. In order to explore the potential of C. fluminea as a natural resource of bioactive compounds, a papain-released polysaccharide designated CFPS-2 was isolated. Chemical composition analysis indicated that CFPS-2 contained glucosamine, glucose, galactose, fucose, protein and sulfate groups, with an average molecular weight of about 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…We previously reported that a C . fluminea sulfate polysaccharide, CFPS-2, displays marked inhibitory effects on the growth of SKOV3 human ovarian carcinoma cells and SGC7901 human gastric cancer cells [2]. Zhu et al reported that another bioactive glycoprotein, CFp-a, from C .…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that a C . fluminea sulfate polysaccharide, CFPS-2, displays marked inhibitory effects on the growth of SKOV3 human ovarian carcinoma cells and SGC7901 human gastric cancer cells [2]. Zhu et al reported that another bioactive glycoprotein, CFp-a, from C .…”
Section: Introductionmentioning
confidence: 99%
“…5-year survival after application of chemotherapy at patients with GC resectable is less than 20% and therefore the effectiveness of chemotherapy is disputed [14]. 5-year survival of the four groups classified by differentiation and depth of penetration in layers is [T2/3 (differentiated type), T2/3 (undifferentiated type), T4a (differentiated type), and T4a (undifferentiated type)] were 98%, 92%, 80%, and 72%, respectively (P < 0.01) [15]. Inhibitory effects on cell Ca growth of the stomach have antioxidant substances like: CFPS-2 containing: Glucosamin, glucose, Galactose, Fructose, protein and sulfate groups [16].…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] PS or PSP can be explored as a functional food or medicine for potential applications in food industry, cosmetics, and pharmacy. However, PS or PSP have yet to be separated and characterized from C. uminea through TPP.…”
Section: -20mentioning
confidence: 99%
“…6a-c and Table 1 Additionally, PSP and E-PSP were different from the previous studies because perhaps of the raw material sources and separation protocols. 21,22 In this work, HPGPC was used to determine the molecular weights (MWs) and molecular weight distribution of PSP and E-PSP, and the results are summarized in Table 1. Both PSP and E-PSP were found to be composed of high-MW fractions (2113.4 kDa and 1980.9 kDa) and low-MW fractions (61.5 kDa and 248.4 kDa).…”
mentioning
confidence: 99%